Key Factors of Stunting Prevalence: Configurational Analysis of Sub-Districts in Sleman, Indonesia - Prasetya Utomo, Puguh (Policy & Governance Review, 2024)
This study employs crisp-set Qualitative Comparative Analysis (csQCA) to examine the determinants of stunting prevalence in 17 sub-districts of Sleman Regency. Addressing the critical issue of stunting, the research aims to identify factors contributing to high and low stunting prevalence. Methodologically, this study advances the application of csQCA in public health research by uncovering the complex interplay of conditions affecting stunting rates, demonstrating its utility in identifying precise causal configurations. Findings reveal that high stunting prevalence is uniquely caused by poor stunting management performance, making it both necessary and sufficient. Moreover, the study elucidates the concept of asymmetric causality by demonstrating that low stunting prevalence results from diverse combinations of high stunting management performance and advanced village development, thereby contributing to a nuanced understanding of causality in public health research. This study not only underscores the need for multi-dimensional strategies but also enriches the WHO framework by methodologically enhancing the identification of necessary and sufficient conditions for effective stunting management, offering a refined approach to tackling complex public health challenges. The research provides valuable insights for policymakers to develop comprehensive stunting reduction strategies, focusing on improving stunting management and fostering village infrastructure development.